Investigation of high-pressure planetary ices by cryo-recovery. I. An apparatus for X-ray powder diffraction from 40 to 315 K, allowing ‘cold loading’ of samples - Wood, Ian G. (J Appl Crystallogr, 2018)
A low-temperature stage for X-ray powder diffraction in Bragg–Brentano reflection geometry is described. The temperature range covered is 40–315 K, with a temperature stability at the sample within ±0.1 K of the set point. The stage operates by means of a Gifford–McMahon (GM) closed-cycle He refrigerator; it requires no refrigerants and so can run for an extended period (in practice at least 5 d) without intervention by the user. The sample is cooled both by thermal conduction through the metal sample holder and by the presence of He exchange gas, at ambient pressure, within the sample chamber; the consumption of He gas is extremely low, being only 0.1 l min(−1) during normal operation. A unique feature of this cold stage is that samples may be introduced into (and removed from) the stage at any temperature in the range 80–300 K, and thus materials which are not stable at room temperature, such as high-pressure phases that are recoverable to ambient pressure after quenching to liquid nitrogen temperatures, can be readily examined. A further advantage of this arrangement is that, by enabling the use of pre-cooled samples, it greatly reduces the turnaround time when making measurements on a series of specimens at low temperature.